Pengaruh Pengelolaan Uang Saku dan Modernitas Individu Terhadap Perilaku Konsumtif Peserta Didik - Safira, Billa; Riani, Dini; Sanjaya, Firman (Universitas Pendidikan Ganesha, 2025)
This study was motivated by the rising phenomenon of consumptive behavior among adolescents, particularly high school students, which is influenced by modern lifestyles and a lack of financial management skills. The objectives of this study are: (i) to determine the level of pocket money management, individual modernity, and consumptive behavior among students, and (ii) to analyze the influence of pocket money management and individual modernity on students’ consumptive behavior both partially and simultaneously. This research employed a quantitative approach using a survey method. The subjects of the study were 10th-grade students at SMA Pasundan 2 Bandung, with a total sample of 78 respondents selected through purposive sampling. The results revealed that: (i) students' pocket money management was at a moderate level, individual modernity was categorized as high, and consumptive behavior was also at a high level; (ii) there is a negative and significant influence between pocket money management and consumptive behavior, with a significance value of 0.000 < 0.05; (iii) there is a positive and significant influence between individual modernity and consumptive behavior, with a significance value of 0.032 < 0.05; and (iv) there is a significant simultaneous influence of pocket money management and individual modernity on students’ consumptive behavior. This study recommends enhancing financial literacy education and fostering wise consumption attitudes among students to help them manage their finances rationally and avoid falling into consumptive lifestyle traps.